Mouse Microglial Calcitonin Receptor Knockout Impairs Hypothalamic Amylin Neuronal pSTAT3 Signaling but Lacks Major Metabolic Consequences - Bernd Coester; Thomas A. Lutz; Christelle Le Foll (Metabolites, 2022)
Amylin and leptin synergistically interact in the arcuate nucleus of the hypothalamus (ARC) to control energy homeostasis. Our previous rodent studies suggested that amylin-induced interleukin-6 release from hypothalamic microglia may modulate leptin signaling in agouti-related peptide expressing neurons. To confirm the physiological relevance of this finding, the calcitonin receptor (CTR) subunit of the amylin receptor was selectively depleted in microglia by crossing tamoxifen (Tx) inducible Cx3cr1-CreERT2 mice with CTR-floxed mice. Unexpectedly, male mice with CTR-depleted microglia (KO) gained the least amount of weight of all groups regardless of diet. However, after correcting for the tamoxifen effect, there was no significant difference for body weight, fat mass or lean mass between genotypes. No alteration in glucose tolerance or insulin release was detected. However, male KO mice had a reduced respiratory quotient suggesting a preference for fat as a fuel when fed a high fat diet. Importantly, amylin-induced pSTAT3 was decreased in the ARC of KO mice but this was not reflected in a reduced anorectic response. On the other hand, KO mice seemed to be less responsive to leptin’s anorectic effect while displaying similar ARC pSTAT3 as Tx-control mice. Together, these data suggest that microglial amylin signaling is not a major player in the control of energy homeostasis in mice.